2013
DOI: 10.1242/jeb.087395
|View full text |Cite
|
Sign up to set email alerts
|

Superficial neuromasts facilitate non-visual feeding by larval striped bass (Morone saxatilis)

Abstract: SUMMARYTo investigate whether mechanoreception is used in non-visual feeding in larval striped bass (Morone saxatilis), the ontogeny of superficial neuromasts along the lateral line was described using the vital stain FM1-43FX and fluorescent microscopy. The number of neuromasts visible along one flank increased from 11 at first feeding [5 to 7days post-hatch (dph)] to >150 by the juvenile stage (27dph). A neomycin dose response (0, 1, 2 and 5mmoll) was evaluated for neuromast ablation of bass aged 10, 13,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…The lateral line system is a hydrodynamic sensory system found in fishes and aquatic amphibians (Bleckmann & Zelick, 2009). More recently, Sampson, Jim, and Croll (2013) reported the evidence that superficial neuromasts likely mediate non-visual feeding in larvae of Morone saxatilis. Yanase, Herbert and Montgomery (2014) reported that superficial neuromasts unilateral ablation, produced directional instability of steady swimming and altered propulsive movements, suggesting a role for sensory feedback in correcting yaw and slip disturbances to maintain efficient locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…The lateral line system is a hydrodynamic sensory system found in fishes and aquatic amphibians (Bleckmann & Zelick, 2009). More recently, Sampson, Jim, and Croll (2013) reported the evidence that superficial neuromasts likely mediate non-visual feeding in larvae of Morone saxatilis. Yanase, Herbert and Montgomery (2014) reported that superficial neuromasts unilateral ablation, produced directional instability of steady swimming and altered propulsive movements, suggesting a role for sensory feedback in correcting yaw and slip disturbances to maintain efficient locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…This antibody has been shown to specifically mark axons in zebrafish Danio rerio (Hamilton 1822), the goldfish Carassius auratus (L. 1758) and other teleosts (Trevarrow et al , ; Varatharasan et al , ; Newton et al , ). Axons were also revealed by antibodies against pan‐α‐tubulin and acetylated‐α‐tubulin, which mark microtubules in the axons of teleosts (Varatharasan et al , ; Sampson et al , ) and other animals. In an attempt to label specific types of sensory cells that are found in a variety of vertebrates (Fano et al , ), antibodies against calretinin and S100 calcium‐binding proteins were used.…”
Section: Methodsmentioning
confidence: 99%
“…It is not surprising, therefore, that a myriad of sensory cell types are associated with the skin. Possibly the most well studied is the lateral line, a system of mechanoreceptor-based sensory organs that detect changes in water pressure, thus aiding in detection of prey and predators (Bleckmann & Zelick, 2009), non-visual feeding (Sampson et al, 2013) and water flow (Montgomery et al, 2000;Ghysen & Dambly-Chaudière, 2004). One such key sensory organ is the superficial neuromast that is located on the skin surface.…”
Section: Introductionmentioning
confidence: 99%